Semantic structure and structure of the sentence - Елеуовa А. С.; Зинедин, А. С. (Journal of Oriental Studies, 2018)
The article, based on the works of researchers, determines the features of the intrasemantic composition of the sentence and the grammatical category of its components. The author notes that such syntactical parts of the sentence do not always coincide as the subject, predicate, complement, definition and circumstance and such semantic notions of the sentence as the subject, predicate, object, attribute and concretizer, and proceeding from this, concludes that it is necessary to implement semantic analysis of the sentence. All these phenomena are also characterized by the material of the Kazakh language.